Influences of a relative assistant support during labor at Aparicio Pomares Health Center Huánuco 2004-2005 - Manrique de Lara Suárez, Digna (2017)
The study was carried out in the Center of Health Aparicio Pomares whose demand of childbirth attention yearly is approximately 500 childbirths. The investigation had as main objective to determine the influence of the accompaniment from a relative to the gestante during the childbirth work. The investigation type was basic, of descriptive, analytic, prospective, longitudinal method, of descriptive design and correlacional, with a sampling non probabilísticoforconvenience, and are presentative sample of 30% (150) childbirths. The materials and used methods were the interview and observation guides in dilation room and it salts of childbirth. The obtained results were: Regarding the age, 30% is from 15 to 23 years. 34,7% didn't have prenatal control; 23,3% is primigestas; regarding the reduction of the pain and estrés 83,3% is given on the part of the mother; 62,6% during the childbirth work demonstrated that thecompanion's support promotes a positive experience and gratificante; in 92% he/she decreased the time of childbirth work; in an average of 80% they showed security and trust, biggerstrength;theydidn'tpresentcomplicationsneitherunnecessaryinterventions and they collaborated with the obstetric personnel, 96,6% it demonstrated better affective bond with their baby and their relative (I handcuff). There fore you concluded that the accompaniment of a relative  during the childbirth work is positive because it allows this sublime stage of all woman that is to bring a boy totheworld, to conclude satisfactorily especially because the responsibility is not assumed alone for the professional but it is shared with the family.